2019
DOI: 10.1111/evj.13131
|View full text |Cite
|
Sign up to set email alerts
|

Administration of enrofloxacin during late pregnancy failed to induce lesions in the resulting newborn foals

Abstract: Summary Background A recent study demonstrated that enrofloxacin and ciprofloxacin cross the equine placenta without causing gross cartilage or tendon lesions in the 9‐month fetus; however, long‐term effects of in utero fluoroquinolone exposure remain unknown. Objectives To assess effects of fetal exposure to enrofloxacin on the resulting foal's cartilage and tendon strength. Study design and methods Healthy mares at 280 days’ gestation were allocated into four groups: untreated (n = 5), therapeutic treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 19 publications
3
20
0
Order By: Relevance
“…While our concurrent study showed that enrofloxacin and its active metabolite (ciprofloxacin) cross the equine placenta without causing gross or histological lesions in foals born from mares treated during late pregnancy, 3…”
Section: Introductionmentioning
confidence: 74%
“…While our concurrent study showed that enrofloxacin and its active metabolite (ciprofloxacin) cross the equine placenta without causing gross or histological lesions in foals born from mares treated during late pregnancy, 3…”
Section: Introductionmentioning
confidence: 74%
“…No gross or microscopic lesions were noted in the articular cartilage collected from the 5-week-old foals in either treatment groups nor were any differences in tendon strength noted between the treatment and control groups [18]. However, gross articular lesions were noted in multiple joints of the two positive control foals in the study; these foals were treated with 10 mg/kg of enrofloxacin per os, once daily for 7-10 days starting at 2 and 3 weeks of age [18]. In this complementary study, administration of enrofloxacin in late pregnant mares did not cause tendinopathies or articular damage in the resulting foals examined at 5 weeks of age.…”
mentioning
confidence: 87%
“…As anticipated, detectable maternal plasma concentrations of enrofloxacin and ciprofloxacin were noted throughout the treatment period; unexpectedly, both of these drugs were still detectable in the amniotic and allantoic fluids 30 – 40 days after administration of the last oral dose of enrofloxacin. No gross or microscopic lesions were noted in the articular cartilage collected from the 5‐week‐old foals in either treatment groups nor were any differences in tendon strength noted between the treatment and control groups . However, gross articular lesions were noted in multiple joints of the two positive control foals in the study; these foals were treated with 10 mg/kg of enrofloxacin per os, once daily for 7 – 10 days starting at 2 and 3 weeks of age .…”
mentioning
confidence: 92%
See 2 more Smart Citations